Blind-sided homicide where it is least expected - Moffatt, Gregory K. 1961- (Praeger, 2000)
This book explains why friends and colleagues who knew the perpetrators of violence overlooked or misunderstood warning signs, and it addresses the role that mental illness often plays in such crimes. Chapters are devoted to homicide in the workplace, domestic homicide, stalkers who kill, and homicide by children, including an entire chapter on the Columbine High School shooting. Using his experience as an educator, researcher, and clinician, Moffatt demonstrates how to identify the historically non-violent murderer through a process of risk assessment before a crime is committed. He also describes seven common mistakes people make that have resulted in one or more deaths.